2011
DOI: 10.1007/s10464-011-9424-3
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Model of Racial Discrimination, Acculturative Stress, and Cultural Resources Among Arab American Adolescents

Abstract: Despite evidence towards the risk for discrimination and acculturative stress that Arab American adolescents may face, the link between socio-cultural adversities and psychological well-being in this population has not been established. This study examined the role of socio-cultural adversities (discrimination and acculturative stress) and cultural resources (ethnic identity, religious support and religious coping) in terms of their direct impact on psychological distress. Using structural equation modeling, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
120
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(140 citation statements)
references
References 57 publications
18
120
2
Order By: Relevance
“…First, the results of the study found that acculturation and acculturative stress significantly predicted psychological problems. These results align with the previous research showing an association between acculturation, acculturative stress, and psychological problems across a variety of ethnic minority and/or immigrant groups (Lopez, Ehly, & Garcia-Vazquez, 2002) as well as with Arab American adolescents (Ahmed et al, 2011). Immigrant or ethnic minority groups who maintain their cultural traditions and values may experience fewer psychological problems because they are able to identify with, and feel a part of, their ethnic community (Greene, Way, & Pahl, 2006).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…First, the results of the study found that acculturation and acculturative stress significantly predicted psychological problems. These results align with the previous research showing an association between acculturation, acculturative stress, and psychological problems across a variety of ethnic minority and/or immigrant groups (Lopez, Ehly, & Garcia-Vazquez, 2002) as well as with Arab American adolescents (Ahmed et al, 2011). Immigrant or ethnic minority groups who maintain their cultural traditions and values may experience fewer psychological problems because they are able to identify with, and feel a part of, their ethnic community (Greene, Way, & Pahl, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…Being a member of a religious community, perceiving support from God, and practicing their religion may be protective factors from the stress of acculturation for these adolescents. Previous research with Arab American adolescents suggested that religious coping and support play an important role in the process of acculturation (Ahmed et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include difficulties in obtaining employment, social exclusion, harassment and suspicion. Several studies have pointed towards the role of religion in coping with these acculturative challenges Ahmed, Kia-Keating, & Tsai, 2011;Aydin et al, 2010;Gardner et al, 2014). Aydin et al 's (2010) study of Turkish-German Christians and Muslims facing racial discrimination and segregation found religious coping to significantly buffer the effects of acculturative stress on wellbeing.…”
Section: The Role Of Religion In Coping With Stressmentioning
confidence: 99%